Peculiarities of Conducting Practical Classes in the Discipline «Methods of Teaching Geography» - Oksana Voitovych (Pedagogical Discourse, 2020)
The article considers the peculiarities of conducting practical classes in the discipline «Methods of Teaching Geography» for students majoring in «Secondary education (Geography)». It is substantiated that the topics of practical work and the content of the proposed tasks should take into account current trends in education and the requirements for the training of a competent teacher. The structural elements of the practical lesson are determined: the theme of the lesson, the purpose, the equipment, the tasks of the classroom work, which reflect the questions for discussion and practical tasks; tasks for independent extracurricular work, the list of recommended reading. It is established that the content of the practical task should be professionally oriented, which helps to increase the internal motivation of the student to study. The following sequence of practical classes is recommended: introductory speech of the teacher indicating the importance of the topic of practical work and defined tasks for the future professional activity, checking completed tasks for self-education, discussing theoretical issues and clarifying practical tasks, performing practical tasks by students, evaluating completed tasks, closing tutor’s remarks in order to summarize and make recommendations for further work. It has been found out that the main forms of practical classes in the discipline are frontal and individual. The content of practical work «Methods of Preparing a Geography Teacher for Lessons» is given.It has been argued that the success of practical classes depends on students’ understanding of the scope of certain tasks of a particular practical work, involving students in active activities to solve practical problems, professional orientation of certain tasks, implementation of active learning methods, taking into account individual abilities.